RELATIONSHIP AMONG TYPE OF SCHOOL, ACADEMIC RESILIENCE AND ACADEMIC ACHIEVEMENT AMONG SECONDARY SCHOOL STUDENTS IN KIAMBU COUNTY, KENYA - Mwangi, Cecilia Nyambura; Ireri, Anthony Muriithi; Mwaniki, Elizabeth W; Wambugu, Stephen K (PEOPLE: International Journal of Social Sciences, 2018)
This study investigated the relationship among type of school, academic resilience and academic achievement among secondary school students in Kiambu County, Kenya. A descriptive correlational design was used. A randomly selected sample of 390 students in the third year of secondary education was involved. The participants were drawn from four categories of secondary schools: Boys boarding, girls boarding, coeducational boarding and coeducational day. Data were collected using a demographic form and the California Healthy Kids Survey (CHKS) resilience scale. A significant mean difference (F (3,386) = 9.39, p < .05) was reported in the academic resilience scores when type of school was considered. The difference was in favour of girls’ boarding schools. The mean academic resilience and achievement for boys’ boarding was found to be significantly lower than that of girls’ boarding, boys’ day, and mixed day secondary schools. It was recommended that educational stakeholders should shift from considering type of school as being peripheral to academic outcomes and instead regard it as a key contributor to the educational outcomes of secondary school students.